Access to Justice: Protecting Spousal Health from Sexually Transmitted Diseases Transmission within Marriage - Irawati, Jovita; Andiani, Angie; Anthony Wijaya (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
This study explores how Indonesia’s present regulatory framework navigates to protect spousal health from Sexually Transmitted Diseases (STDs) transmission within marriage. Employing a normative legal approach which combines statutory analysis and comparative methods. The analysis focuses on Indonesia’s regulatory framework. Findings reveal that the current regulations including the Constitution 1945, Health Law, Marriage Law, Elimination of Domestic Violence Law, Criminal Code, various Regional Regulations and Regulation of The Minister of Health. These regulations provide limited coverage of instances where individuals jeopardies the health of others, particularly spouses, through the transmission of STDs. Comparative analysis of Singapore, Cambodia, Brunei Darussalam, and the United Kingdom demonstrate a common emphasis on informed consent and risk mitigation, often achieved through criminalization of non-disclosure of HIV status. However, the study acknowledges the limitations of such punitive approaches in achieving sustainable public health outcomes. The conclusion proposes moving beyond the current framework. It suggests leveraging the Health Law’s framework for family health promotion and its association with disease control. This could involve establishing a regulatory system grounded in scientific research, prioritizing a consensual and holistic approach cantered on comprehensive education and prevention programs. This approach recognizes STDs as a social issue requiring collective action, contrasting with the tendency in some neighboring countries to view them solely as a medical concern. By addressing these legal gaps and fostering responsible sexual health practices within marriage, Indonesia can contribute to a healthier and more secure marital environment for its citizens.